Analytical description of hadronic integral spectra of cosmic-ray superfamilies with Feynman scaling breaking - Bellandi, J. [UNESP]; Costa, C. G.S. [UNESP]; Covolan, R. J.M. [UNESP]; Dobrigkeit, C. [UNESP]; Mundim, L. M. [UNESP]; Salles, C. [UNESP] (American Physical Society (APS), 1994)
We describe charged hadronic energy spectra of the cosmic-ray superfamilies named Ursa Maior and P3'-C1-B90, detected by the Chacaltaya and Pamir Emulsion Chamber Collaborations, respectively, using analytical solutions for the diffusion equations. We obtain a very good description of these events incorporating Feynman scaling breaking in the multiparticle production model of our cascading formalism. Centauro exotic events are also investigated. © 1994 The American Physical Society.